Identification and Prevalence of Endoparasites in Timor Deer (Cervustimorensis) at Maliran Deer Captive Breeding Blitar - Khairunnisa, Anindita; Lastuti , Nunuk Dyah Retno; Sugihartuti , Rahmi; Setiawan, Boedi; Koesdarto , Setiawan; Wardhana, Dhandy Koesoemo (Faculty of Veterinary Medicine Universitas Brawijaya, 2023)
Deer populations in captive breedings have the potential to develop health issues such as protozoa and helminth infections. Poor sanitation and environmental conditions are among the external factors facilitate the transmission of endoparasites within deer population in a captivity. The aim of this study was to identify and determine the prevalence of endoparasite infestation in Timor deer (Cervus timorensis) in Maliran Captive Breeding, Blitar, Indonesia. Samples of 102 fresh feces, were taken during the rainy season from March to May 2021, and sent to Laboratory of Parasitology, Veterinary Medicine Faculty, Universitas Airlangga for fecal examination using sedimentation, flotation, as well as McMaster methods to determine the prevalence and the intensity of infestations. Results showed that 30 samples were detected positive, 7 samples (6.86%) were positive of Haemonchus spp. at the egg stage (range of 30-60 EPG; mild infestation); and 23 samples (22.55%) were positive of Eimeria spp. in oocyst stage (range of 200-800 OPG; mild to moderate infestation). This study provides a reference for the eradication of Haemonchiasis in the deer population in the study area.